(3eHGOF aj GdYdGbGJ GdYGeI (B/s - (3GdMdHj,MSf s ((3HjQhJ (B:s (3efThQGJ YhjOGJ ,s, 1980)
(3Jbhe GdYdGbGJ GdYGeI Ydi GdZJUGd HGdLeghQ aj SHjd Ndb JhGab h GfSLGe GaVd Hjf GdGTNGU h GdCTjGA aj fWGb GdeDSSI Gh GdMeGYI Gh GdeLJeY(B.(3h GfgG JQJcR HUhQI Ydi GRGdI GdGdJHGS h ShA GdJaGge Hjf GdGOGQI h LeghQgG Yf WQjb JMOjO eUGdMgG h eUGdMg ceG JQej Gdi GRGdI hGbY GdLgd Gh fbU GdeYdheGJ Yf GdLeghQ h GHOGdg HGdGYdGe GdcGed GdPj jgjA ddLeghQ eLGd Jchjf QCjg HMQjI hhGbYjI h dEOGQI GecGfjI GdMUhd Ydi KbI GdLeghQ h JCjjOgs
Keywords: (3GdYdGbGJ GdYGeIs